MHD Stagnation-Point Flow with Viscous Dissipation and Chemical Reaction Effects: Numerical Study - Srisailam, B.; Reddy, K. Sreeram; Narender, G.; Malga, Bala Siddulu (Communications in Mathematics and Applications, 2023)
In this article, a numerical study of the magnetohydrodynamics flow with heat and mass diffusion of an electrically conducting stagnation point flow past a shrinking/stretching sheet with chemical reaction of diffusing species and internal heat absorption/generation is analyzed. Flow equations are modified to a system of non-linear Ordinary Differential Equations (ODE) by using the similarity transformations. Numerical solution of the Ordinary Differential Equations (ODE) is found by using the shooting technique with Adam’s Moulton method of order four. Finally, the results are discussed for different parameters affecting the flow and transfer of heat.